IMMUNE ORGANS AND GROWTH PERFORMANCE OF MALE LAYING HENS WITH USE OF EUGENOL CLOVE LEAF OIL AS A SUBSTITUTE OF ANTIBIOTIC IN FEED - Hafsah Hafsah; A P Damayanti; Syahrir Syahrir; Tahir Tahir; Feni Rahmasari; M R Alsahab (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
The use of antibiotics as growth promoters (AGP) in poultry feed aims to stimulate growth and prevent disease. However, the use of antibiotics in animal feed has been banned spread of resistant bacteria which can be harmful to human health. The use of natural compounds, especially essential oils, as a natural alternative for antibiotics. The aim of the study was to evaluate the inclusion of eugenol clove leaf oil as a feed additive to replace antibiotics in feed on immune organs and growth performance of male laying hens. Experiment was designed in Completely Randomized Design with 5 treatments and 4 replicates. The study Animal used 120 DOC (Day Old Chick) of male laying hens. Treatments consist of: P1 = Basal feed; P2 = Basal feed + 0.005% tetracycline ; P3 = Basal diets + 0.5% eugenol; P4 = Basal diets + 1.0% eugenol; P5 = Basal diets + 1.5% eugenol. Variables observed i.e.: immune organs (thymus, bursa fabricus, spleen, liver) and growth performance (weigh gain, feed intake, protein intake, energy intake, feed efficiency). The statistical analyses were carried out using Anova and LSD test. Results were shown high significant (P<0. 01) effects on thymus (immune organ) and growth performance (weight gain, feed intake, protein intake, energy intake, feed efficiency) of male laying hens. However, no significant (P>0.05) effects on bursa fabricus, spleen, and liver (immune organs). Our finding suggest that the use of eugenol clove leaf oil as a substitute for antibiotics in feed, with a level of 0.5%-1.0% of male laying hens resulted similar response to the use of tetracycline 0.005%.